Bevacizumab Combined with Corticosteroids Does Not Improve the Clinical Outcome of Nasopharyngeal Carcinoma Patients With Radiation-Induced Brain Necrosis - Li, Honghong; Rong, Xiaoming; Hu, Weihan; Yang, Yuhua; Lei, Ming; Wen, Wenjie; Yue, Zongwei; Huang, Xiaolong; Chua, Melvin L. K.; Li, Yi; Cai, Jinhua; He, Lei; et al. (Frontiers in Oncology, 2021)
Objective: To compare the clinical outcome of patients treated with bevacizumab combined with corticosteroids to bevacizumab monotherapy from a radiation-induced brain necrosis (RN) registry cohort (NCT03908502). Methods: We utilized clinical data from a prospective RN registry cohort (NCT03908502) from Jul. 2017 to Jun. 2020. Patients were considered eligible if they had symptomatic RN after radiotherapy for NPC and received bevacizumab (5mg/kg, 2 to 4 cycles) with a minimum follow-up time of 3 months. The primary outcome was a 2-month response rate determined by MRI and clinical symptoms. Secondary outcomes included quality of life (evaluated by WHOQOL-BREF scale) and cognitive function (evaluated by Montreal Cognitive Assessment scale) at 2-month, RN recurrence during follow-up, and adverse events. Results: A total of 123 patients (34 in the combined therapy group and 89 in the monotherapy group) were enrolled in our study with a 0.97 (IQR 0.35-2.60) years median follow-up time. The clinical efficacy of RN did not differ significantly between patients in these two groups (OR 1.642, 95%CI (0.584- 4.614), p=0.347). Furthermore, bevacizumab combined with corticosteroid didn’t reduce the recurrence compared with bevacizumab monotherapy (HR 1.329, 95%CI (0.849-2.079), p=0.213). The most common adverse events of bevacizumab were hypertension (17.89%), followed by nosebleed (8.13%), and fatigue (8.13%). There was no difference in grade 2 or severer adverse events between the two groups (p=0.811). Interpretation: Our results showed that the treatment strategy of combining bevacizumab with corticosteroid did not lead to better clinical outcomes for RN patients with a background of radiotherapy for nasopharyngeal carcinoma.